DINAMIKA DAN PROBLEMATIKA ASURANSI SYARIAH: Mekanisme Kerja Asuransi Syariah & Prosedur Pembayaran Klaim - Sulistyowati, Sulistyowati (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam UIN Sunan Ampel Surabaya, 2012)
The mechanism of action of sharia insurance is essential to distinguish between Shariah insurance with conventional insurance lies in how the work is done from the premium deposits, investment funds, to the payment of insurance claims to participants stricken or disaster. Everything is summed up in the concept of the working mechanism Shariah insurance. Discussion about the mechanism of action or Shariah insurance, will be divided in two basic discussion in accordance with Shariah insurance payment itself, the family insurance and insurance Shari'ah common. This division is very important to do considering the mechanism of action of these two Shariah suransi it memuliki little difference, namely in the management of premiums paid to insurance companies Shari'ah. Difference arises because